Real-world effectiveness of Semaglutide treatment on weight loss maintenance after weight loss in patients with obesity or overweight and diabetes - Michela Del Prete; Lidia Gavazzi; Olga Eugenia Disoteo; Federico Vignati; Gianleone Di Sacco; Fabrizio Muratori (Eating and Weight Disorders)
Abstract Purpose To report data on the real-world effectiveness and safety of injectable (IS) and oral (OS) therapies in obese or overweight diabetes (T2DM) patients on glycometabolic control, weight loss (WL) and weight maintenance after the use of semaglutide. Methods 175 subjects with obesity or overweight and T2DM were retrospectively assessed. Of these, 129 (75F, 54 M; mean age 61.2 ± 9.8 years) patients were treated with IS and 46 (24F, 22 M; mean age 65.7 ± 12.8 years) with OS for T2DM and WL. At baseline, mean weight (mW) was 101.8 ± 24.6 kg and 95.2 ± 15.0 kg; mean body mass index (mBMI) was 36.7 ± 8.7 kg/m2 and 34.3 ± 5.3 kg/m2. Results After 6 months, in the IS group, 127 patients had a mW and mBMI reduction of − 10.4 ± 8.1 kg and − 3.9 ± 3.0 kg/m2. 46 patients in the OS group had a mW and mBMI reduction of − 6.7 ± 5.3 kg and − 2.6 ± 2.1 kg/m2. After 12 months, 102 patients in the IS group achieved a mW and mBMI reduction of − 9.3 ± 7.5 kg and − 3.4 ± 2.6 kg/m2. 44 patients in the OS group of treatment had a mW and mBMI reduction of − 10.7 ± 6.5 kg and − 3.9 ± 2.4 kg/m2. After 24 months, 92 patients in the IS group of therapy achieved a mW and mBMI reduction of − 15.9 ± 11.4 kg and − 5.8 ± 3.7 kg/m2. There was a mean percentage reduction of glycated hemoglobin (HBA1C) of − 1.9 ± 1.4%, − 1.5 ± 1.9%, and − 1.5 ± 1.7% after 6, 12 and 24 months in the IS group. In the OS group there was a mean reduction of − 1.5 ± 1.6% after 6 months and of − 0.8 ± 0.6% after 12 months of therapy. Conclusions Semaglutide induces WL maintenance after 12 and 24 months of treatment. Our results show a comparable effectiveness of IS and OS in T2DM patients with obesity or overweight. IS and OS treatment provide significant WL that allows reaching the glycometabolic therapeutic goal in a short time. Level of Evidence Level II